Awareness of Vitamin D Deficiency among the General Population in Jeddah, Saudi Arabia - Lujain H. Alamoudi; Rinad Z. Almuteeri; Murooj E. Al-Otaibi; Dalia A. Alshaer; Samar K. Fatani; Maha M. Alghamdi; Osama Y. Safdar (Journal of Nutrition and Metabolism)
Background. During the last decade, vitamin D status was a major concern in the health and biomedical fields. This study assessed the level of awareness and knowledge regarding vitamin D and investigated the factors associated with the level of awareness such as knowing general facts about vitamin D, sources, benefit, and consequences of its deficiency. Methods. This cross-sectional study was conducted among the general population in Jeddah, Saudi Arabia, above the age of 18 years who were in 3 malls during the period of August and September 2017. A self-administrated questionnaire in paper forms was utilized and was divided into two parts to collect data. It was designed by the authors after revising the previous studies and validated by three pediatric consultants. An ethical approval was obtained from the ethical committee in King Abdulaziz University. We did an initial sample and tested it with the Cronbach test. The questionnaire had 2 parts with 19 questions. The first part was demographic information, and the second part was general information about vitamin D. An ethical approval was obtained from the ethical committee in King Abdulaziz University. Each participant received explanations about the aim of the study, and a verbal consent was taken from participants. The scoring system was as follows: for each right answer, 1 score was given and for wrong answer, 0 score was given, and the overall score was 14. The collected data were statistically analyzed using descriptive statistics using IBM SPSS statistics for windows version 20.0 (SPSS Inc., Chicago, IL). Result. Out of 1022 participants, 472 (46.1%) were aged 18–28 years, 830 (82.1%) were of Saudi ethnicity, 702 (68.7%) had a university degree, 275 (26.9%) attended high school, more than half were married (55.6%), and 54.4% had children. The majority of the participants agreed that vitamin D is important in the maintenance of bone and tooth health (88.4%). It is important in the maintenance of calcium and phosphates (76.6%), and it strengthens immunity (69.4%). Of the total participants, 86.2% were aware that sunlight exposure encourages vitamin D production in the skin. The overall knowledge mean score was 5.9 ± 1.2 (39.3%). Conclusion. This study highlighted a high level of inadequate knowledge of vitamin D deficiency among participants. There was a significant association between knowledge level and education level. The awareness of vitamin D deficiency is high regarding its benefits. The study revealed that participants who did not have children had the highest score for benefits. Nongovernment organizations and social workers may work together with government health-care organization to teach parents and children about the uses and benefits of vitamin D.